The witches of Ochagavía and documentation on them - de la Nogal Fernández, Rocío (Huarte de San Juan. Geografía e Historia, 2010)
Through the correspondence between the Court of the Inquisition in Calahorra and the Council of the Inquisition, this article aims to study the focal point of witchcraft which came to a head in Ochagavía and other localities in the Valley of Salazar at the beginning of 1539. In addition to reconstructing the trials of faith initiated against the witches of Ochagavía, our objective is to reveal how the Holy Office worked in Navarre by relating the proceedings of the Court of the Inquisition in Calahorra not only with those of Navarre’s courts of law, but also with the directives and guidelines set by the Supreme Court and other Bodies of the Spanish monarchy.
Keywords: Inquisition; Witchcraft; Navarre; Ochagavía; Valley of Salazar; Trials of faith; Trials; Jurisdiction